OUR EXPERIENCE IN THE TREATMENT OF VITILIGO WITH TRANSPLANTATION OF EPIDERMOCYTES OF OUR OWN SKIN - Vaisov, A.Sh.; Fuzaylov, D.N.; Munir Ahmad, Munir Ahmad; Umarov, J.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: A clinical assessment of the effectiveness of the technology for producing epidermocytes of the skin and their transplantation onto depigmented skin areas. Material and methods: Under observation were 28 patients (19 women, 9 men) with various forms of vitiligo aged 19-35 years with 48 foci of vitiligo with disease duration from 4 to 15 years; Duration of patient monitoring – 12 months. The distribution of patients according to skin phototypes according to Fitzpatrick showed that with III skin phototype there were 22 patients; with phototype II – 6. Results: Treatment with transplanted uncultured epidermal cells in 28 patients with vitiligo included several stages. Dermabrasion of the lesion was performed by a dermabrider. Epidermal grafts for transplantation were obtained by cutting off the covers of the blisters obtained at a negative pressure of 200-300 mm RT. Art. After 10-12 PUVA sessions, 19 patients showed complete repigmentation of 19 foci; repigmentation in 75-80% of the area – in 15 foci; on 50% of the area – in 10 outbreaks, less than 50% - in 4 outbreaks. The greatest effect was obtained in patients with localization of foci of depigmentation on the trunk and proximal limbs and with III skin phototype. The achieved result was maintained throughout the observation period (12 months). Conclusions: The use of the method of transplantation of epidermocytes of their own skin in the treatment of various forms of vitiligo is an affordable and very promising method of therapy, which allows to achieve a pronounced lasting effect without complications.